Ravaged Ecology, Cruel Displacement, Impoverished Livelihoods - Naumen, Muhammad (Water Nepal, 2003)
The Chotiari Reservoir Project is no different from other water related mega projects executed in Pakistan, though it exhibits a greater degree of human rights violations ecological destruction and poor governance. Unless the historical rights of the affected communities are legally recognised and the allocation of water is based on equitable shares for all communities irrespective of their class, social and political background, their human rights and environment will remain unprotected. The issue of good governance is related to this question: ‘Who controls the political power?’ The extension of democratic processes to the grassroot level and the strength of democratic institutions and public participation in the functioning of institutions could serve as the lever for the promotion and protection of human rights and progress. Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.313-318